Which was Written First: Asrār al-balāga or Dalāil al-i’jāz? A Study on Determining the Writing Dates of the Two Works - İsmail Araz (Şarkiyat Mecmuası)
In this research, the aim is to determine the timeline for the creation of the works Asrār al-balāga and Dalāil al-i’jāz by the 11th-century scholar ʿAbd al-Qāhir alJurjānī (d. 471/1078-1079). Al-Jurjānī did not specify which of these works, which encompassed poetry criticism, rhetoric, and i’jāz, was composed first. This lack of clarity has led to the debate on whether Asrār was written before Dalāil. Over the years, researchers have approached this issue primarily through implied evidence, leaving room for speculation and avoiding definitive conclusions. In contrast, this study is grounded in a manuscript that provides crucial insights into the timing of Dalāil’s composition. The study begins by presenting the perspectives of researchers on this topic and subsequently conducts a thorough analysis of significant copies of Dalāil. Within this framework, notable conclusions about al-Jurjānī’s scholarly pursuits were drawn by scrutinizing the information in the manuscript, which conveys the statements of a contemporary of al-Jurjānī named Abû Zayd from Jurjān. This pioneering study aims to enhance our understanding of al-Jurjānī’s scholarly endeavors and objectives by identifying the chronology of Asrār and Dalā’il, recognized as fundamental sources of rhetoric.